Firm Productivity and Economic Growth in Turkey - World Bank (Washington, DC: World Bank, 2019)
Turkey’s pace of income convergence has globally been one of the most remarkable of the past fifteen years. Sustaining growth and improvements in living standards in Turkey will require higher productivity in the economy. The Turkey Productivity Report (2019) provides an in-depth analysis of firm productivity in Turkey and how this adds up to economic growth in the country. The report has six parts. The first two provide macro and micro diagnosis of productivity in the economy – what are the productivity trends, how have these affected economic growth, what firms in what industry are the most productive, and are they absorbing an increasing or decreasing share of resources? From here the report analyzes specific policy areas that might explain firm productivity dynamics in Turkey – namely firms’ integration in the global economy, access to innovation support, the quality of human capital, and the business environment including competition. The report finds that economic integration and innovation have boosted firm-level productivity, though reforms could further accelerate these positive impacts. Productivity gains could accelerate the demand for more educated and skilled workers. The growth of more productive firms could in turn also be accelerated through reforms that increase competition and reduce regulatory burden.